Stimulus intensity determined by dose-titration versus age-based methods in electroconvulsive therapy in Thai patients - Pichai Ittasakul (2020)
© 2019 Ittasakul et al. Objectives: This study aimed to compare the accuracy of the stimulus intensity (SI) calculated by age-based methods with that using the dose-titration method. Methods: The initial seizure threshold (IST) was determined using a standardized dose titration in hospitalized Thai patients treated with right unilateral (RUL, n=32) and bilateral (BL, n=57) electrode placement. The correlation between the IST and clinical variables was analyzed. The estimated SI based on the patient’s age was compared with the SI determined by dose titration. Results: Age was highly predictive of the IST for both groups (RUL, P=0.012; BL, P=0.045). Gender (P=0.006) and anticholinergic drug use (P=0.025) predicted the IST for the BL group. For the RUL group, the mean±SD (median) SI estimated using the half-age and age methods was 158±46 (169) mC and 315±92 (338) mC, respectively. The SI determined using the dose-titration method was higher compared with the half-age method and lower compared with the age method. For the RUL group, 31% of subjects using the half-age method and 22% of subjects using the age method would have received an SI within ±20% of that computed using dose titration. Additionally, 19% of subjects using the half-age method and 19% using the age method would have received unacceptably low (<50%) or high (>200%) intensities. For the BL group, 18% of subjects using the half-age method and 32% using the age method would have received an SI within ±20% of that computed using dose titration. Additionally, 39% with the half-age method and 18% with the age method would have received an unacceptably low or high SI, respectively. Conclusion: Age strongly predicts the IST, but it does not robustly predict the SI compared with dose titration because the SI calculated using age-based methods results in an unacceptably low or high SI that is associated with a marked risk of adverse effects or inadequate response. We recommend the dose-titration method to determine the SI.